Metode Penyelesaian Dalam Kajian Matan Hadis-Hadis Kontroversial - Abd Rahman R (Jurnal Adabiyah: Humanities and Islamic Studies, 2014)
This writing discusses controversial hadits and the way of understanding the hadis, using various methods and interpretation technique. Although a hadis is recognized controversial, it doesn’t mean that it cannot be solved. Some ulamas of hadis have discussed and put forward some alternative arguments to come to final conclusion. Some methods such as; al-Jam'u, al-Tarjih, al-Nasikh, wa al-Mansukh dan al-Tauqif, as well as  textual, contextual interpretation, linguistic or historical approach  can be regarded  as ways to understand the essentian meaning of the controversial hadis.